The Influence of Knowledge And Supervision Techniques on Nurses’ Compliance With The Implementation of Early Warning Score (EWS) With Work Attitude As An Intervening - Nurwarwiyah; Wahyuni Dian Purwati; Rina Anindita (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Patient safety is a top priority in hospital services, one of which is achieved through the implementation of early detection systems such as the Early Warning Score (EWS) to prevent the deterioration of patients’ clinical conditions. However, nurse compliance in applying EWS remains a challenge, as observed at Annisa Hospital Cikarang.Objective:To analyze the influence of knowledge and supervision techniques on compliance with EWS implementation, with work attitude as an intervening variable. This study employed a quantitative method with a cross-sectional approach. The index analysis was conducted using the Three Box Method, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The population comprised all nurses working in the Emergency Department (ED) and inpatient wards at Annisa Hospital Cikarang. A total sampling technique was applied, resulting in 100 respondents. The findings revealed that, simultaneously, knowledge, supervision techniques, and work attitude significantly influenced compliance with EWS implementation. Partially, knowledge and supervision techniques also had a positive effect on work attitude. Furthermore, work attitude was proven to mediate the effect of knowledge and supervision techniques on nurse compliance. The Three Box Method analysis indicated that although the compliance index was categorized as high, weaknesses persisted in the dimensions of professional responsibility and timely reporting